A boundary value problem with an integral condition for a certain fractional differential equation - Hammou, Bouthina Sabah; Djerad, Abdelkader; Memou, Ameur; Latrous, Chahla (Mathematical modelling and analysis, 2025)
The aim of this work is to prove the existence and the uniqueness of the solution of one dimensional initial boundary value problem for a parabolic equation with a Caputo time fractional differential operator supplemented by periodic nonlocal boundary condition and integral condition. First, an a priori estimate is established for the associated problem. Secondly, the density of the operator range generated by the considered problem is proved by using the functional analysis method.